IMPLIKASI PARLIAMENTARY THRESHOLD TERHADAP SISTEM KEPARTAIAN DI INDONESIA - Okta Yuda Adiwira (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2020)
The main topic of discussion in this journal is the application of the parliamentary threshold policy in the political system in Indonesia. The Parliamentary threshold is a minimum vote acquisition threshold that must be met by political parties participating in the elections to be able to place their legislative candidates in parliament. The juridical empirical research method is used for discussion, which includes the effectiveness and impact of the law. This study also aims to provide input or contribution of ideas to the central government in implementing the parliamentary threshold policy on political parties, so as to produce good governance (good governance) that is stable, effective and efficient. Based on the research results, it can be seen that there is a parliamentary threshold debate in the political system in the country regarding the threshold for national vote acquisition for political parties to be included in the calculation and distribution of DPR seats. In formal juridical terms, the parliamentary threshold debate in the party system in Indonesia is conducted based on the law on political parties and democratic principles. The application of the parliamentary threshold in the national political system is expected to be simplified. Simplifying the number of political parties in Indonesia needs to be done as an effort to improve the quality of political parties so that they can make better contributions to the development of national politics. In addition, party simplification is also carried out in order to facilitate political governance in parliament and to increase the effectiveness and efficiency of democratic and political processes both in parliament and in government. Therefore, simplifying the party is an alternative solution in improving the quality of democracy and government stability, which in the end is for the welfare of the people.